The Role Of Housewives To Improve The Family Economy By Utilizing Oil Palm Sticks In Koto Aman Village, Kabupaten Kampar, Riau - Aumalia Hanipah; Rahmi Syahriza; Khairina Tambunan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research endeavors to examine the contribution of homemakers in enhancing their family's financial status by utilizing oil palm sticks. Currently, at PT Buana Wiralestari Naga Mas Div 2/3, the sticks from oil palm fronds are treated as waste, thus tarnishing the cleanliness of the oil palm plantation. Employing a qualitative approach with a descriptive method, data collection involves structured interviews with predetermined questions, direct observation of the phenomenon in the field, and documentation. The findings reveal that oil palm plantations serve as the primary source of employment and income for residents of Pt. Wira Lestari Mas division 2/3. However, the replanting process affects income, prompting many homemakers to seek additional earnings by selling sticks or converting palm frond waste into economically valuable products like broomsticks. This initiative not only yields economic benefits but also contributes to social welfare by offering useful products and enhancing environmental cleanliness. Nevertheless, fluctuating stick prices and obstacles such as the rainy season, festive occasions, and inadequate support from local authorities and PT regulations impede homemakers' endeavors in stick utilization. This underscores the significant role of homemakers in household and local economic advancement, emphasizing the importance of price stability and support from the government and community for sustained economic well-being.